Integrasi Etnobotani Dayak dalam Pengembangan Bahan Ajar Keanekaragaman Hayati untuk Sekolah Menengah Atas - Fadil Muhammad; Hartono; Hartati; Firdaus Daud; Syamsiah (Jurnal Penelitian Pendidikan IPA, 2026)
Biodiversity learning in senior high schools is often abstract and weakly connected to students local socio-ecological realities. Local ethnobotanical knowledge can provide a contextual basis for more meaningful biodiversity learning. This study aimed to develop and evaluate Dayak ethnobotany-based biodiversity teaching materials for Grade X students. The study used a Research and Development design with the ADDIE model. The participants were 23 tenth-grade students from one intact class and two biology teachers at SMA Negeri 1 Uut Murung, Central Kalimantan, Indonesia. The student sample represented a limited field trial to examine the feasibility and initial effectiveness of the product in a real classroom context. Data were collected using expert validation sheets, teacher and student response questionnaires, and learning outcome tests with a one-group pretest-posttest design. Product validity using Gregory’s formula obtained a score of 1.00, indicating very high validity. Practicality scores reached 95,5% from teachers and 91,5% from students. Learning outcomes increased from 47.25 to 89.86, with an N-Gain score of 0.83, categorized as high. The greatest improvement occurred in students cognitive understanding of biodiversity, especially its relationship with the local environment and local wisdom-based in conservation. Thus, the teaching materials are valid, practical, and effective for contextual biodiversity learning.